Math, asked by Grandpig, 6 hours ago

sin A + sin B + sin(A + B)÷
sin A + sin B - sin(A + B)

Answers

Answered by SuzanneDsouza
4

Answer:

Ans: 0

Step-by-step explanation:

sin(A−B)

+

sinBsinC

sin(B−C)

+

sinCsinA

sin(C−A)

=0

=

sinAsinB

sinAcosB−cosAsinB

+

sinBsinC

sinBcosC−cosBsinC

+

sinCsinA

sinCcosA−cosCsinA

=cotB−cotA+cotC−cotB+cotA−cotC

=0 (proved)

Answered by IIYourFirstDeathII
22

Answer:

OMG

Imma big fan of yours

I won't miss this opportunity

International Soviet Internet Spammers

Step-by-step explanation:

Similar questions